School principals' transformational leadership behaviours and their effects on teacher commitment - Balyer, Aydin; Karatas, Hakan; Alci, Bulent (ICLEL CONFERENCES, 2016)
Transformational leadership has drawn much attention in the educational administration field. It has four basic areas in educational settings such as idealized influence, inspirational motivation, individualized consideration and intellectual stimulation. Research indicates that school principals' transformational leadership behaviours have positive and direct effects on teachers' performance and feeling commitment. Therefore, this qualitative study purposes to determine the teachers' views of their principals' transformational leadership behaviors and their influences on their feeling of commitment. The research employed a qualitative research design. The participants of the study were 40 teachers from 10 selected successful schools in Istanbul, Turkey. Results indicate that, in general, school principals' transformational leadership behaviors are positively related to teachers' commitment. It was also determined that while principals' inspirational motivation, intellectual stimulation and individualized consideration behaviors are positively related to teachers' commitment, idealized influence is not related to it. In can be recommended that school principals should perform transformational leadership behaviors to increase teachers' commitment.
Keywords: transformational leadership; school principals; teacher commitment; 5-FACTOR MODEL; PERSONALITY; Education & Educational Research